PSIKOEDUKASI MENINGKATKAN KUALITAS PENGAJARAN GURU SEKOLAH MINGGU DENGAN MEMAHAMI PERKEMBANGAN ANAK DI THE GRACE PAKUAN YOGYAKARTA - Lidiawati, Krishervina Rani; Theresia, Allessandra; Anggreany, Yuliana; Helsa, Helsa; Aurelia, Trisha (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
This Community Service Activity (PKM) aims to enhance the teaching quality of Sunday school teachers at The Grace Pakuan Yogyakarta through psychoeducation focused on understanding child development. Recognizing the need for information on teaching methods that consider developmental stages, the Faculty of Psychology at UPH initiated an educational program addressing developmental stages and specific cases encountered by Sunday school teachers. The program includes a series of workshops and training sessions designed to equip teachers with knowledge of child development and effective teaching techniques. By understanding cognitive, emotional, and social developmental stages, teachers are expected to create more engaging, supportive, and effective learning environments. The psychoeducation program includes both pre-test and post-test evaluations to measure changes in teachers' knowledge about child development. Evaluations reveal significant improvements in understanding the developmental stages of Sunday school children and children with special needs. These findings suggest that the psychoeducation program can be extended to include training for new teachers to help them comprehend child development stages and develop teaching methods that are easily understood by Sunday school children. Additionally, there is a need for continuous programs aimed at creating inclusive and effective Sunday school environments within the church.